The effects of stocking density, prey concentration and feeding on Rhinelepis aspera (Spix & Agassiz, 1829) (Pisces: Loricariidae) larviculture - doi: 10.4025/actascibiolsci.v34i2.8541 - José Cláudio Epaminondas dos Santos; Marcelo Mattos Pedreira; Ronald Kennedy Luz (Acta Scientiarum. Biological Sciences, 2011)
The aim of this study was to evaluate three stocking densities (20, 40 and 60 larvae L-1), and two daily prey concentrations (400 and 700 Artemia nauplii larvae-1) during the first seven days of active feeding (first phase). In the second phase was evaluate the effect of the different feeding regimes: fasting, dry diet (55% crude protein), Artemia sp. and mixed feeding (Artemia sp. plus dry diet), after 17 days of active feeding on Rhinelepis aspera larviculture. In the first phase, growth was affected only by prey concentration. In the second phase, the dry diet induced higher growth rates than fasting, but lower growth rates than the other treatments. The acceptance of the dry diet was evidenced by an increase in the growth rate from 4.6% day-1 in the first five days to 10.7% day-1 in the following five days of feeding. Survival was similar among dry diet, mixed feeding and Artemia nauplii treatments. R. aspera larvae can be reared during the first seven days of active feeding at a density of 60 larvae L-1, after which they can be fed with a commercial dry diet.